2009
DOI: 10.1002/ijc.24947
|View full text |Cite
|
Sign up to set email alerts
|

Identification of G0S2 as a gene frequently methylated in squamous lung cancer by combination of in silico and experimental approaches

Abstract: Epigenetic changes can lead to abnormal expression of genes in cancer, and several genes have been reported to have aberrant promoter DNA methylation in non-small-cell lung cancer (NSCLC). We identified aberrantly methylated genes in NSCLC by combination of in silico and experimental approaches. We first applied bioinformatics, and from microarray datasets, we selected genes with low expression and having functions related to cancer. Next, combined bisulfite restriction analysis was carried out in 10 pooled re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 45 publications
2
36
0
Order By: Relevance
“…7 Hypermethylation of the G0S2 promoter was found in primary head and neck squamous cell carcinoma, primary squamous lung cancer, and also in squamous lung cancer cell lines. [8][9][10] This epigenetic silencing of G0S2 in diverse types of cancer strengthens the case for G0S2 acting as a tumor suppressor. In vitro modification of G0S2 levels has shown little impact on cell growth, apoptosis or differentiation (unpublished data and Kusakabe et al).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…7 Hypermethylation of the G0S2 promoter was found in primary head and neck squamous cell carcinoma, primary squamous lung cancer, and also in squamous lung cancer cell lines. [8][9][10] This epigenetic silencing of G0S2 in diverse types of cancer strengthens the case for G0S2 acting as a tumor suppressor. In vitro modification of G0S2 levels has shown little impact on cell growth, apoptosis or differentiation (unpublished data and Kusakabe et al).…”
Section: Introductionsupporting
confidence: 53%
“…[7][8][9][10][16][17][18] However, its functions are still not well understood. To explore G0S2 function in vivo, G0S2 −/− mice were generated and characterized (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although several reports have indicated that CIMP is also distinguishable in NSCLC and is associated with a poor prognosis, (27,28) we have failed to distinguish the phenotype in the previous study regarding the methylation of the promoter regions of numerous protein-coding genes. (29) In the present study, we analyzed whether the concordant hypermethylation of multiple miRNA loci results in characteristics similar to those of CIMP. The methylated status of two or more miRNA loci was found to be associated with a significantly higher risk for advanced T status independent of age, sex, and smoking habit.…”
Section: Discussionmentioning
confidence: 99%
“…These results also imply that p53 expression is not necessary for the antiproliferative effects of pioglitazone in NSCLC cells as H1299 cells do not express p53. G0S2 has been found to be frequently methylated in SCC of the lung (41), suggesting that G0S2 may have tumorsuppressive functions in the context of lung SCC. Additional mechanisms, such as induction of differentiation (24,25,27), inhibition of invasion, and inhibition of angiogenesis, may also be significant (23).…”
Section: Discussionmentioning
confidence: 99%